SNOW COMPACTION - DESIGN CRITERIA AND TEST PROCEDURES. - Moser,E. H. ,Jr. (1964)
Techniques and equipment are presently available for producing high-strength snow capable of supporting wheeled aircraft with tire inflation pressures up to 75 psi and gross weights up to 75,000 lbs. Current investigations in Antarctic are directed toward increasing the load-bearing capacity of compacted-snow runways on deep perennial snowfields up to 150,000 lbs. Existing criteria are given for the design of compactedsnow roads and runways on annual and perennial snowfields. The limitations of these criteria require that they be applied with judgment. Improved test equipment, instruments, and procedures are being developed to test the properties and trafficability of compacted snow. (Author)